GEOFFREY YEO, Records, Information and Data: Exploring the Role of Record-Keeping in an Information Culture - Cunningham, Adrian (Archivaria, 2020)
Records, Information and Data: Exploring the Role of Record- Keeping in an Information Culture. Geoffrey Yeo. London: Facet Publishing, 2018. xvi, 208 pp. ISBN 978-1-78330-226-0